CCR5 is a novel target for the treatment of experimental alopecia areata - Taisuke Ito; Takahiro Suzuki; Atsuko Funakoshi; Toshiharu Fujiyama; Yoshiki Tokura (Frontiers Media S.A., 2020)
Abstract Background Alopecia areata (AA) is an organ‐specific and cell‐mediated autoimmune disease. Hair follicle autoantigens are disclosed to these autoreactive NKG2D+CD8+ T cells. A Th1 chemokine, CXCL10, is highly expressed on hair follicle keratinocytes and leads to the infiltration of CXCR3+ and CCR5+ Th1 or Tc1 cells around anagen hair follicles in AA lesions. Aim To evaluate CCR5 as a new candidate target for the treatment of experimental AA. Methods We initiated 7‐month‐old female C3H/HeJ mice with intracutaneous injections of lymph node (LN) cells, which were activated by IL‐2, IL‐7, IL‐15, and CD3/CD25 Dynabeads, from C3H/HeJ mice with spontaneous AA. Then, 330 μg/d of maraviroc, a negative allosteric modulator of the CCR5 receptor that is already used for treating patients with human immunodeficiency virus, was orally administrated for 28 days. Results We successfully treated the experimental AA lesions of C3H/HeJ mice with maraviroc. In addition, CCR5 blockade prevented the development of AA in activated T cell‐transferred C3H/HeJ mice. Interestingly, maraviroc‐treated C3H/HeJ mice with experimental AA showed improvement of hair loss lesions after 2 weeks. Immunohistological assessments and FACS analysis revealed a decreased number of CD4+CCR5+ and CD8+CCR5+ T cells in the lesions after maraviroc treatment. A real‐time horizontal chemotaxis assay showed that maraviroc significantly inhibited the chemotactic activity of CD8+ LN cells toward RANTES. Furthermore, CCR5 blockade prevented experimental AA development when compared to phosphate‐buffered saline. Conclusion CCR5 appears to be a promising new candidate target for the treatment of AA. CCR5 blockade may prevent the development of AA as well as improve AA lesions.